Diminished sarco/endoplasmic reticulum Ca²⁺ ATPase (SERCA) expression contributes to airway remodelling in bronchial asthma - Mahn, Katharina; Hirst, Stuart J; Ying, Sun; Holt, Mark R; Lavender, Paul; Ojo, Oluwaseun O; Siew, Leonard; Simcock, David E; McVicker, Clare G; Kanabar, Varsha; Snetkov, Vladimir A; O'Connor, Brian J; et al. (Proceedings of the National Academy of Sciences - PNAS, 2009)
Phenotypic modulation of airway smooth muscle (ASM) is an important feature of airway remodeling in asthma that is characterized by enhanced proliferation and secretion of pro-inflammatory chemokines. These activities are regulated by the concentration of free Ca²⁺ in the cytosol ([Ca²⁺]i). A rise in [Ca²⁺]i is normalized by rapid reuptake of Ca²⁺ into sarcoplasmic reticulum (SR) stores by the sarco/endoplasmic reticulum Ca²⁺ (SERCA) pump. We examined whether increased proliferative and secretory responses of ASM from asthmatics result from reduced SERCA expression. ASM cells were cultured from subjects with and without asthma. SERCA expression was evaluated by western blot, immunohistochemistry and real-time PCR. Changes in [Ca²⁺]i, cell spreading, cellular proliferation, and eotaxin-1 release were measured. Compared with control cells from healthy subjects, SERCA2 mRNA and protein expression was reduced in ASM cells from subjects with moderately severe asthma. SERCA2 expression was similarly reduced in ASM in vivo in subjects with moderate/severe asthma. Rises in [Ca²⁺]i following cell surface receptor-induced SR activation, or inhibition of SERCA-mediated Ca²⁺ re-uptake, were attenuated in ASM cells from asthmatics. Likewise, the return to baseline of [Ca]i after stimulation by bradykinin was delayed by approximately 50% in ASM cells from asthmatics. siRNA-mediated knockdown of SERCA2 in ASM from healthy subjects increased cell spreading, eotaxin-1 release and proliferation. Our findings implicate a deficiency in SERCA2 in ASM in asthma that contributes to its secretory and hyperproliferative phenotype in asthma, and which may play a key role in mechanisms of airway remodeling.